Pemanfaatan Akun TikTok Oleh ANTARA News Sebagai Sarana Penyebaran Informasi dan Berita Kriminalitas Terhadap Perempuan - Nandita Arifin; Andhika Pamungkas; Tellys Corliana (SENTRI: Jurnal Riset Ilmiah, 2025)
The dissemination of information about crimes against women through social media has become an important issue in line with the increasing consumption of digital information among the public. ANTARA News, as a national news agency, utilizes the TikTok platform to reach a broader audience and effectively convey sensitive issues. This study aims to understand how ANTARA News uses its TikTok account @antaranews as a means to disseminate information and news related to crimes against women. The research employed a descriptive qualitative approach and a case study method. Data were collected through in-depth interviews, observation, and documentation of uploaded content. The results show that content packaging strategies are carefully executed, taking into account journalistic ethics and TikTok's community guidelines. Meanwhile, the gatekeeping process involves pre-production, production, and post-production stages conducted collaboratively among creators, editors, and unit heads. These findings indicate that the successful dissemination of sensitive information on social media relies not only on technology but also on communication strategies and adaptive editorial policies. This study highlights the importance of the role of new media in supporting the safe and responsible delivery of information, especially regarding women's issues.